Adsorption Isotherm Of O-cresol From Aqueous Solution By Granular Activated Carbon. - Maarof, Hawaiah Imam; Hameed, Bassim H.; Ahmad, Abdul Latif (2003)
Equilibrium adsorption isotherms of o-cresol from aqueous solution were investigated by a series of laboratory batch studies.